Lack of Homozygously Inactivated p73 in Single-Copy MYCN Primary Neuroblastomas and Neuroblastoma Cell Lines - Xiao-Tang Kong; Virginia A. Valentine; Susan T. Rowe; Marcus B. Valentine; Susan T. Ragsdale; Bart G. Jones; Deborah A. Wilkinson; Garrett M. Brodeur; Susan L. Cohn; A. Thomas Look (Neoplasia: An International Journal for Oncology Research, 1999)
We examined 18 neuroblastoma cell lines and 32 primary single-copy MYCN tumor specimens to determine whether mutations of p73, a novel p53-related gene located in chromosome band 1p36.33, contribute to the genesis or progression of childhood neuroblastoma. By fluorescence in situ hybridization, 16 of the 18 cell lines, but only 3 of the 32 primary tumors, had evidence of a deleted p73 allele. Sequence analysis of the p73 coding region in the mRNAs expressed by these cell lines and tumors did not reveal inactivating mutations, suggesting that p73 is not homozygously inactivated in neuroblastoma. However, several novel splice forms of p73 mRNAs were identified, including one without exon 11 that predominated in multiple MYCN-amplified cell lines. Its encoded p73 protein differed from other splice forms in that the C-terminus was derived from an alternative reading frame. Further study of the functional properties of the protein encoded by this splice form of p73 will be needed to determine whether it contributes to the pathogenesis of childhood neuroblastoma with MYCN gene amplification.